Forfatteroversigt. Navne og kontaktoplysninger om bidragydere - Schjørring, Jens Holger; Bradley, S. A. J.; Lundgreen-Nielsen, Flemming; Pedersen, Kim Arne (Grundtvig-Studier, 2005)
List of authors’ adresses